Analisis Strategi Pengelolaan Keuangan Usaha Kerajinan di Objek Wisata Ke’te Kesu’ - Arlianti La’biran; Elisabeth Pali; Jemi Pabisangan Tahirs (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The aim of this research is to find out how financial management strategies include planning, recording, reporting and controlling. This type of research is descriptive qualitative. The type of data used is primary data, namely data obtained or collected directly in the field through interviews with related information showing that the results of the financial management strategy for craft businesses in Kesu' sub-district, North Toraja district do not implement financial management consisting of planning, recording, reporting and control.